2021
DOI: 10.1079/pavsnnr202116019
|View full text |Cite
|
Sign up to set email alerts
|

Sex selection techniques and their implications

Abstract: Sex selection techniques provide economic benefits to dairy and beef herd management. Therefore, the development of such techniques has attracted the attention of reproductive biologists. There have been numerous studies concerning the development of sex selection techniques. As the sex of the offspring is determined by certain chromosomes, namely the X and Y chromosomes in mammals, most studies have focused on sperm sexing, attempting to separate the X and Y chromosome-bearing sperm based on differences in de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 84 publications
0
2
0
Order By: Relevance
“…While Albumin filter sperm fraction one had higher motility than values in sperm fractions two, three and control samples, respectively. The percentage of rabbit's X chromosome bearing spermatozoa determined by Hoechst stain before and after filtrations are presented in Figure (3). The analysis of variance showed significant differences (P≤0.05) due to the treatments and their interactions in percentage of X chromosome bearing spermatozoa.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…While Albumin filter sperm fraction one had higher motility than values in sperm fractions two, three and control samples, respectively. The percentage of rabbit's X chromosome bearing spermatozoa determined by Hoechst stain before and after filtrations are presented in Figure (3). The analysis of variance showed significant differences (P≤0.05) due to the treatments and their interactions in percentage of X chromosome bearing spermatozoa.…”
Section: Resultsmentioning
confidence: 97%
“…These results are similar with that recorded by Galarza et al (2018), who reported that Sephadex filtration enriched the Y chromosome in ram semen. Also, Naniwa and Uchiyama (2021) reported that Albumin gradient increased ratio of the Y chromosome in cattle semen. An effective method of sex preselection is required depending on the small difference in DNA content that exists between X-and Ychromosome bearing sperm.…”
Section: Discussionmentioning
confidence: 97%
“…A flow cytometer is commonly used in separating spermatozoa, with a success rate of more than 90% of calves born with expected sex. Flow cytometry method procedure: sperm containing the X chromosome and sperm containing the Y chromosome are stained with fluorescence, separated from each other by analyzing differences in DNA content, and frozen [5].…”
Section: Introductionmentioning
confidence: 99%